ASSESSMENT OF THE VALUE OF COMPULSORY INSURANCE OF CROPS IN POLISH AGRICULTURE IN THE LIGHT OF THE ACT ON SUBSIDIES TO INSURANCE OF CROPS AND FARM ANIMALS - Wicka, Aleksandra (Acta Scientiarum Polonorum. Oeconomia, 2009)
The agricultural production in Poland is infl uenced by many risks, which make the effects of such activity uncertain. One of the methods used to manage such a risk is to insure plant and animal production. Such an insurance was used on a voluntary basis. Since July 2008 the crop protection is compulsory with regard to the farmers who use the direct payments. The paper aims to present the potential value of insurance premium connected to plant production, which might be collected by the insurers due to the compulsory insurance. There was also assessed the conjectural value of insurance premiums collected by the insurers under the minimal protection level of farmers. Moreover, the regional differences of demand for insurances were presented. The paper argues that due to new regulations that are come in force in 2009 there is an urgent need for further researches on agricultural insurances in Poland.